Bahasa Gaul di Media Sosial: Kajian Morfologi - Audina, Fitra; Aspinda, Lili; Nasution, Safira Ulya; Astuti, Widia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to analyze the use of slang language on social media and its connection to standard language. The method used is qualitative descriptive with data analysis techniques through observation and field notes. Linguistic theories, especially morphology and syntax theories, are used in this research. The results show that the use of slang language on social media is connected to standard language, both in terms of morphology and syntax. Although slang language contains many loanwords from foreign languages and uses many abbreviations or acronyms, its usage has its own rules that follow the general structure of the Indonesian language. Therefore, slang language on social media can be considered as a form of language variation or style used by people in social interactions on social media.